Utilización de cuatro sustratos para la captura de microorganismos eficientes autóctonos de montaña en una zona protegida en la parroquia Patricia Pilar año 2019. - Triana Brito, William Israel (2020)
The research aimed at developing four substrates for the capture of native efficient microorganisms from a protected area in the Patricia Pilar parish, located at kilometer E 25 of the Vía Buena Fe, Santo Domingo, Santa María Del Toachi Route, province of The rivers. A completely randomized block design (DBCA) was used, it was composed of four treatments, four repetitions and four experimental units per repetition, a total of 64 traps were used for capture. Morphological characterization variables were evaluated at the laboratory level, concentration of microorganisms with greater presence in the substrates and an economic analysis was carried out. The results indicated the population growth of lactic bacteria in the different treatments; varying these are white, yellow, greenish and grayish white; Numerous bacterial populations were found for every 100 g that each treatment contained, however T4 (Barley 50 g + molasses 50 g) was the treatment to record the highest average while the lowest was reflected in T3 (Wheat 50 g + molasses 50 g ); and regarding the economic analysis, T1 (Rice 50 g + meat 50 g) was the treatment that presented the highest cost and the highest income between treatments, however the benefit / cost ratio was the same in each of the substrates elaborated. Keywords: substrates, mountain microorganisms, capture, protected area